2022
DOI: 10.1177/21582440221085263
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Work Ethics, Affective Commitment, and Employee’s Performance in Family Business: Testing Their Relationships

Abstract: A family business is usually managed and run by family members to form and pursue a business vision that will ensure continuity across generations. Subsequently, this study aims to scrutinize and inspect the effect of Islamic work ethics on affective commitment and employee performance. Out of 273 questionnaires that were disseminated to employees of family businesses in Pati, Batang, and Demak districts of Central Java, Indonesia, 147 were filled out and completed questionnaires, reflecting a response rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 128 publications
(164 reference statements)
2
15
0
1
Order By: Relevance
“…The study found that work ethics are significantly correlated with organizational commitment and turnover intention. The same result is also found in the studies of Ud Din, et al (2019), Athar, et al (2016), Udin, et al (2022), Aflah, et al (2021), and bin Salahudin, et al (2016 which work ethic affects job performance, job satisfaction, and organizational commitment.…”
Section: The Concept Of Work Ethicssupporting
confidence: 81%
“…The study found that work ethics are significantly correlated with organizational commitment and turnover intention. The same result is also found in the studies of Ud Din, et al (2019), Athar, et al (2016), Udin, et al (2022), Aflah, et al (2021), and bin Salahudin, et al (2016 which work ethic affects job performance, job satisfaction, and organizational commitment.…”
Section: The Concept Of Work Ethicssupporting
confidence: 81%
“…Transaction is an economic or financial event involving at least two parties (a person with a person or several other people) who exchange each other, involve themselves in lending and borrowing business associations and others on a consensual basis or a legal provision basis based on applicable sharia (Putra, 2022;Zafar & Sulaiman, 2021). The transaction referred to *Corresponding author: Taufik Hidayat, Muhammadiyah University of West Sumatra E-mail: 85taufik@gmail.com in this study is an economic event in the form of buying and selling process carried out by farmers (Azmin et al, 2018;Udin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Work ethic is a person's attitude and behaviour towards work which includes seriousness, perseverance, discipline, creativity, and innovation at work (Mussner et al, 2017); (Udin et al, 2022) and (Syahputra & Satrya, 2021). A high work ethic can affect the productivity and quality of products produced by MSMEs (Ausat, Widayani, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%